THE EFFECTS OF FLOMOXEF SODIUM ON PLATELET FUNCTION AND BLOOD COAGULATION - NAKAGAMI, KAZUKIYO; SUZUKI, HAJIME; SHIMIZU, SUSUMU; AKIZAWA, TAKANORI; NARUSHIMA, MICHIAKI; TERADA, HIDEO; TAKAGI, HAJIME; OHTSUKA, HIDEHIKO; KATSUMURA, YUKIO; NOGUCHI, EISEI; TANAKA, KAZUMASA (CHEMOTHERAPY, 1990)
Recently, a bleeding tendency during the administration of antibiotics has been given attention. We studied the effects of flomoxef sodium (FMOX), a new class of oxacephem antibiotic, on platelet function and blood coagulation. The subjects were 12 cases of respiratory tract infections. FMOX was administered by drip infusion at a dose of 2 g /day for 7 days. And the following parameters were measured before and after the administration: platelet count, bleeding time, platelet adhesiveness, platelet aggregation activity, platelet ATP release activity, prothrombin time, active partial thromboplastin time, serum fibrinogen, fibrin degradation products, thrombo test, hepaplastin test, clotting factors II·VII·IX·X, PIVKA-II As a result of this study, there was no deterioration in the platelet function and blood coagulation tests. In 2 cases, however, PIVKA-II was positive. We could not prove any vitamin K deficiency in other parameters and the patients had, normal prothrombin values. We thought on this study that the significance of PIVKA-II is a feature issue. We concluded that FMOX is a safe antibiotic regarding platelet function and blood coagulation at a dose of 2 g /day for 7 days.